2014
DOI: 10.1001/jamaophthalmol.2014.1079
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Adaptive Optics Scanning Laser Ophthalmoscope for Detection of Reduced Cones and Hypoautofluorescent Spots in Fundus Albipunctatus

Abstract: IMPORTANCE Fundus albipunctatus (FA) is a form of congenital stationary night blindness characterized by yellow-white spots, which were classically described as subretinal. Although night blindness and delayed dark adaptation are hallmarks of this condition, recent studies have described a macular phenotype, particularly among older patients. Using a fluorescence adaptive optics scanning laser ophthalmoscope (FAOSLO), this study provides in vivo morphologic data at the cellular level in FA.OBJECTIVE To study t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Using fluorescence AOSLO and cAOSLO, Song et al have reported decreased foveal cone density and increased cone spacing at 10° of eccentricity, despite this predominantly being a rod disorder. 64 No photoreceptors or RPE cells were visualised within the albipunctate spots. Another study also identified decreased perifoveal cone density and mosaic disruption using cAOSLO in RDH5 -associated fundus albipunctatus.…”
Section: Irds and Ao Retinal Ophthalmoscopymentioning
confidence: 97%
“…Using fluorescence AOSLO and cAOSLO, Song et al have reported decreased foveal cone density and increased cone spacing at 10° of eccentricity, despite this predominantly being a rod disorder. 64 No photoreceptors or RPE cells were visualised within the albipunctate spots. Another study also identified decreased perifoveal cone density and mosaic disruption using cAOSLO in RDH5 -associated fundus albipunctatus.…”
Section: Irds and Ao Retinal Ophthalmoscopymentioning
confidence: 97%
“…However, other imaging modes are wavelength dependent. Thus AOSLO systems can be readily adapted for fluorescence imaging of both endogenous (Morgan et al, 2009; Song et al, 2014) and exogenous (Dubow et al, 2014) fluorophores, and for identifying bleachable photopigment using retinal densitometry (Hofer et al, 2005; Roorda et al, 2001; Tuten et al, 2017). However to date there has not been much work using multiply scattered light, which tends to be more sensitive to absorption by retinal pigments (Elsner et al, 1992a; Remky et al, 1996).…”
Section: Adaptive Optics Retinal Imaging Systemsmentioning
confidence: 99%
“…With the AOSLO the most reliable methods for RPE visualization has been to use fluorescence as a contrast mechanism. There are two ways to do this, using the intrinsic fluorescence of lipofuscin (Morgan et al, 2009; Rossi et al, 2013; Song et al, 2014), and using ICG to stain the RPE cells (Tam et al, 2016).…”
Section: Ao Based Measurements Of Retinal Structurementioning
confidence: 99%
“…In patient IV-5, the cone reflectance was diminished relative to surrounding rods, giving them a dark appearance. The presence of these ‘dark cones’ has been described by our group and others in a range of retinal degenerations 17 18 26 and may represent cones with reduced outer segment length or cones that lack outer segments. This hypothesis is supported by split-detector AOSLO that shows preserved cone inner segments underlying dark cones.…”
Section: Discussionmentioning
confidence: 65%
“…Selected study participants (three affected, three unaffected) underwent high-resolution retinal imaging with AOSLO according to published techniques. 17 Cone and rod photoreceptor reflectance images were acquired according to published image acquisition and montaging methods, using 796 nm illumination and a 1.8 Airy disk diameter confocal pinhole. 18 A strip of approximately 10°×1.5° along the nasal meridian was imaged in one eye of each study participant.…”
Section: Methodsmentioning
confidence: 99%